A New TOPSIS Methodology Based on Single-Valued Neutrosophic Numbers for Selection of Suitable Roll Stabilizer Type for Motor Yachts - Sener, Bekir; Balin, Abit; Yildiz, Burak; Demirel, Hakan (SOC NAVAL ARCHITECTS & MARINE ENGINEERS, 2020)
Selection of a suitable stabilization system for motor yachts is a challenging problem for both owners and designers. Also, this is a good sample of multicriteria decision-making problem that includes many criteria required to be assessed at the same time. The present work aims to propose an extended Technique for Order Preference by Similarity to Ideal Solution methodology based on single-valued neutrosophic numbers which represent the uncertainty of real-world applications. A questionnaire was applied to a group of experts who were asked to evaluate four different stabilizer alternatives according to the 15 criteria determined. Evaluations of the experts were analyzed through the proposed methodology, and results were presented and discussed.
Keywords: roll stabilizers; MCDM; TOPSIS; neutrosophic number; GROUP DECISION-MAKING; Engineering